1988
DOI: 10.1039/p29880001699
|View full text |Cite
|
Sign up to set email alerts
|

A surface area approach to determination of partition coefficients

Abstract: A suite of computer programs (AMBER, MS, SURFACE, and GENSTAT) has been used t o calculate the contribution to surface area b y the component atoms of a large number of benzene derivatives containing a variety of substituents such as alkyl, hydroxy, alkoxy, amino, and carbonyl functions (ester, ketone, and aldehyde). We have also considered a wide range of polyaromatic compounds. Component surface areas were related to the measured n-octanol-water partition coefficients ( P ) of the molecules under considerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…If spreading out lipophilicity over a given space is valid, the original logP values should be recovered by integration of the MLR Because the solvent-accessible surface should represent how the molecule is perceived by the environment, it appears to be suited well for integrating the MLP [18,19]. However, a prediction of logP can only be made if a preliminary correlation with experimental lipophilicity is established.…”
Section: Validation Of the Mlpmentioning
confidence: 99%
“…If spreading out lipophilicity over a given space is valid, the original logP values should be recovered by integration of the MLR Because the solvent-accessible surface should represent how the molecule is perceived by the environment, it appears to be suited well for integrating the MLP [18,19]. However, a prediction of logP can only be made if a preliminary correlation with experimental lipophilicity is established.…”
Section: Validation Of the Mlpmentioning
confidence: 99%
“…Various investigators have demonstrated the existence of close correlations between the log P values of organic compounds and their molecular surface area or volume, describing their 'steric' or bulk properties plus the hydrogen-bond donating and accepting properties [43][44][45][46][47][48][49][50][51]. The H20 probe in GRID is an electrically neutral group that has a van der Waals radius of 1.70 A.…”
Section: Partition Coefficients (Log P) Of Furan Analogsmentioning
confidence: 99%
“…To solve this problem, some procedures, such as re-extraction of the aqueous phase before the measurement of concentrations and the use of radiolabeled solutes, have been used to get a satisfactory response with the detector used. 3 In addition to direct measurements, the log P value is often estimated by calculations or by retention parameters derived from reversed-phase HPLC, hereafter referred to as the HPLC method. The most widely used methodology for calculating log P was first proposed by Fujita et al, being based on an additive-constitutive, free energy related property of log P. 4 Thus, by using π defined as the difference in log P between a derivative with a given X substituent (RX) and the parent compound (RH), log P values for multisubstituted compounds might be expressed as:…”
Section: Introductionmentioning
confidence: 99%